Kepemimpinan Kepala Sekolah Dalam Meningkatkan Mutu Pendidikan Di SD 14 Penukal - Anwar, Saipul Anwar; Edi Zalharis; Leny Marlina; Asri Karolina (LP2M IAIN Sultan Amai Gorontalo, 2024)
Abstract An educational institution is greatly influenced by the quality of its quality so that it is known by the community and has an important influence so that the educational institution is attracted by the community to entrust their children to get a good education, therefore researchers are interested in conducting research on the Leadership of School Principals in Improving Quality Education at SD Negeri 14 Penukal. The principal as a leader in an educational institution must have the skills and understand the role he must play for the progress of the school he leads. The progress and decline of an educational institution are greatly influenced by the role of the principal, especially in improving the quality of education in the educational institution he leads, therefore a principal must have appropriate qualifications to enhance the quality of education in the school he leads, by understanding his duties as a leader. The principal can exercise leadership to create a school that is of high quality and has various other achievements. This research uses descriptive qualitative methods with descriptive analysis techniques, namely describing the leadership of school principals to improve the quality of education, supported by evidence of the correctness of existing data. The research aims to find out how school principals carry out their functions in improving the quality of education and to find out how school achievement can be achieved. It is hoped that in the future, after conducting research, it can become reference material for policymakers, especially school principals, in improving the quality of education in the educational institutions they lead. Keywords: Leadership, school principal, quality of education